Penyelidikan KLB Keracunan Makanan di Desa Banjaroyo Kabupaten Kulon Progo - Fatma Nuraisyah (Media Kesehatan Masyarakat Indonesia, 2019)
Based on the report, there are seven people consulted at the health center with the same complaints/symptoms,experiencing diarrhea, abdominal pain, dizziness, heartburn, weakness after consuming food. The purposeof this research is to search for the symptoms and suspected causes of poisoning after consuming food served incelebration event Microhidro May 16, 2014 in Banjaroyo village. This research use case-control study. Cases werepeople who consumed food served during the ceremony who experienced symptoms of diarrhea, abdominal pain,and nausea . Controls were people with no symptomps after consumed food served with age and sex matching.Subjects were interviewed regarding food items consumed. Left-over food items were sent to a laboratory for testing.There were 170 cases. Majority had diarrhea (73%) and abdominal pain (67%). Incubation periods rangedfrom 1 to 16 hours. The epidemic curve was that of a common source outbreak. Sixty cases and 60 controls wereincluded in the case-control study. Food items associated with illness were fried chicken (OR:10.47;95% CI 2.34-46.70) and sambal krecek (OR:6.88; 95% CI 1.38-34.29); these were positive for Staphylococcus. Foods werestored at room temperature with some persons taking food home to share with their families, some of who also gotsick. This outbreak was probably caused by food contaminated with Staphylococcus. The foods could ha ve beencontaminated during preparation and storage.